Analisis profil pelajar pancasila dimensi kreatif di sekolah dasar se-kecamatan ngemplak kabupaten boyolali - Agiza Anastacia Kasna; Supianto Supianto (Didaktika Dwija Indria, 2025)
Abstract. This study aims to describe the of  Pancasila Student Profile  in the creative dimension at elementary schools in Ngemplak Subdistrict, Boyolali Regency. The study used purposive sampling techniue with a quantitative descriptive approach. The sample consisted of three elementary schools, namely SDN 1 Pandean, SDN 1 Sawahan, and SDN 1 Gagaksipat. the Pancasila Student refers to three main elements, namely : 1) generating original ideas, 2) producing original works or actions, and 3) having flexibility in thinking and seeking alternative solutions to problems. These three main elements are further broken down into six indicators, which are assessed through a test consisting of multiple-choice and essay questions. The test comprises 20 multiple-choice questions and 3 essay questions. Each element has a different percentage value, which is categorized into four levels : very good, good, sufficient, and poor. The result showed that out of 204 students, 48% were categorized as good, meaning that these student have good creativity.